Topsis Method for Selection of New Student Admissions at the Faculty of Communication and Information Technology at the National University of Jakarta: Topsis Method for Selection of New Student Admissions at the Faculty of Communication and Information Technology at the National University of Jakarta - Yana Tania Haryanto; Agung Triayudi; Ira Diana Sholihati (Institute of Computer Science (IOCS), 2020)
Selection of new admissions is the usual routine universities every year, this activity is done as a way to get students who have quality standards in accordance with the acceptance criteria determined by the university. However, at the National University in particular on FTKI, admission is actually doing is good enough but the results of the selection has not been implemented to the maximum, making it less optimal data processing activities such selection. Because the need for Decision Support System to be the result of the value of some of the criteria for the standardization of prospective students. In making the decision support system, TOPSIS method is used to determine students based on proper criteria by comparing the level of the quality of each prospective student using TOPSIS calculation will produce a ranking to help become FTKI UNAS selection consideration. The criteria used in this TOPSIS SPK, among others: CBT Computer, Mathematics and Language CBT, CBT Sciences, Interview, Department of the Home School, Home School Accreditation and Average - Average Value UN. The system in this research alternative filter 75 of the total 275 alternative data. The system accuracy up to 82% by making comparisons and calculations manually. CBT Computer, Mathematics and Language CBT, CBT Sciences, Interview, Department of the Home School, Home School Accreditation and Average - Average Value UN. The system in this research alternative filter 75 of the total 275 alternative data. The system accuracy up to 82% by making comparisons and calculations manually. CBT Computer, Mathematics and Language CBT, CBT Sciences, Interview, Department of the Home School, Home School Accreditation and Average - Average Value UN. The system in this research alternative filter 75 of the total 275 alternative data. The system accuracy up to 82% by making comparisons and calculations manually.